THE EFFECT OF LEARNING STRATEGIES AND LEARNING INDEPENDENCE ON LEARNING OUTCOMES IN LEARNING EVALUATION SUBJECT - Rusydi Ananda (State Islamic University of North Sumatra Indonesia, 2019)
Abstract. This study aims to find out and stress: (1) differences in learning outcomes between those taught with collaborative learning strategies with competitive learning strategies, (2) differences in student learning outcomes with different learning independence, and (3) interactions between learning strategies and independence learning about learning outcomes The research instrument is a test used to obtain learning outcomes and questionnaires to obtain data on learning independence. The analysis technique is two-way Anava at significance a = 0.05. The results showed: (1) the average learning outcomes of students taught with collaborative learning strategies = 28.15 higher than those taught with competitive learning strategies = 26.92, with Fcount = 29.57 > Ftable = 3.968, (2) the average student learning outcomes with high learning independence = 29.93 is higher than low learning independence = 25.94 with Fcount = 4.43 > Ftable = 3.968, and (3) there is an interaction between learning and independence learning strategies towards learning outcomes with Fcount = 7.18 > Ftable = 3.968. Keyword: Learning Strategies, Learning Independence, Learning Outcomes